Nationalist ideology, rightwing populism, and public views about climate change in Europe. Issue 7 (10th November 2021) - Kulin, Joakim; Johansson Sevä, Ingemar; Dunlap, Riley E.
ABSTRACT: Rising rightwing populism (RWP) potentially constitutes an obstacle to climate change mitigation, as European RWP parties and politicians often espouse climate change skepticism and oppose climate policies. Meanwhile, their party positions and issue stances have also become increasingly characterized by nationalism. Using European Social Survey data from 2016, we show that public attitudes consistent with nationalist ideology are clearly linked to voting for RWP parties and that people who hold these attitudes are more likely to be skeptical about climate change and to oppose policies that increase taxes on fossil fuels. With regard to policy attitudes, we find that nationalist ideology is more influential than traditional left-right political ideology, environmental values and political trust. The results also reveal substantial cross-national differences, as nationalist ideology is linked more closely to public views about climate change in Western European countries, where RWP parties with a nationalist rhetoric have had recent electoral successes.